Descriptive Analysis of the Factors Leading to Decreased Work Motivation - Wahyudi, Wahyudi (Universitas Pamulang, 2024)
Declining work motivation presents a significant challenge across various sectors, including higher education. This study aims to analyze the factors affecting the decrease in work motivation among lecturers at private higher education institutions in South Tangerang. The research employs a qualitative method with descriptive analysis. Data was collected through a questionnaire distributed to 190 lecturers randomly selected from private colleges in South Tangerang. Descriptive analysis reveals that the main factors influencing decreased work motivation include high workload, lack of recognition, and unclear career paths. These findings provide a deeper understanding of the elements that need to be addressed to enhance motivation.